Effects of pressure on steam turbine performance in a small scale power plant / Bala Murugan Chandiran - Bala Murugan, Chandran (2018)
Power plant consists of 4 main components that determine the efficiency of the whole system. Each component has its own function and there are always room for improvements to increase the efficiency. Advancing the procedure of working condition of power plant impressively enhanced the turbine power output, in which simultaneously reduce the energy consumption. The industrial sector being the biggest player in power plant usage, constantly seeking improvisation and effectiveness of the power plant operation. With the present market trend of continuous rising of fuel and energy prices, reducing the energy requirement has become a top objective. Every minor or major changes in power plant system greatly affect the output. The main objective of this study was to vary the boiler pressure plus turbine pressure and study the efficiency of the steam turbine power output. Therefore, modification and changes were done for the operating conditions of boiler pressure and turbine pressure which influenced the power plant turbine performance significantly. Energy balance of the plant was analysed in the experiment by varying aforesaid parameters. Detailed calculation and analysis had been done for each sets of experiment outcome. Increasing these parameters value influences the steam utilization in the turbines and further increased the turbine effectiveness. The examination done shows that increasing boiler pressure and turbine pressure enhance the power yield of the turbine, efficiency and effectiveness in regular steam control plants. In the end of thesis, the experiment had been conducted successfully and some recommendation had been identified for future research and development.